Multilevel Authentication for Social Network - Dalian Wu Zhia Sheng; Isredza Rahmi A Hamid; Hannani Aman (Society of Visual Informatics, 2018)
Nowadays, social network plays a vital role in communication. Normally user used social networks in daily activities. However, this left all online users susceptible to misuse and abuse. Recently, there has been a remarkable growth in number of hacking as well. Once the computer is online, anyone can have access to the network. Therefore, we proposed a secure social network site called SocialBook where users can post status, photos and connect with friends. This system is developed using PHP programming language and Iterative and Incremental Development methodology.Â The purpose of developing this system is to solve unsecured login accounts and lack of user authentication problem. This system applies the secret question procedure when the user wants to change their account password. Moreover, SocialBook use idle session timeout mechanism for additional security. When the user is idle for ten minutes, they will be logged out automatically. So, the user will be less worry about their account from being hacked and the identity impersonation by unauthorized user.